The use of fluconazole associated with surgical excision in the treatment of equine cutaneous pythiosis - Carvalho, Armando de Mattos; Munhoz, Thayanne Caroline Pereira; Toma, Hugo Shisei; Santos, Jéssica Pamela Velasco dos; Oliveira, Luiz Gustavo Schneider de; Boabaid, Fabiana Marques; Xavier, Andressa Batista da Silveira; Kommers, Glaucia Denise (Semina: Ciências Agrárias, 2019)
Cutaneous pythiosis is an important disease affecting horses raised in regions with a hot climate and water stagnation, occurring throughout all regions of Brazil. The disease progresses rapidly, and treatment for chronic lesions is challenging. The purpose of this study was to evaluate the efficacy of fluconazole after surgical excision and electrocauterization of cutaneous lesions in horses naturally infected with Pythium insidiosum. We treated 10 horses with cutaneous pythiosis, whose diagnoses were confirmed by histopathological and immunohistochemical examinations. After surgical debridement of lesion, animals received fluconazole orally for 21 days, in combination with topical treatment for the wounds. After 7 days of therapy, there was decreased serosanguineous secretion and no kunkers in the wounds in all horses. All lesions healed completely after therapy, and there were no recurrences 10 months after discharge. When associated with surgical excision, oral fluconazole therapy was an effective treatment in clinical cases of equine cutaneous pythiosis.